Ali Baba y los 40 ladrones = Ali Baba and the 40 thieves - Blade, Domenec (Lincolnwood, Ill., National Textbook Co., 2000)
Tales and legends is a collection of legends and classic stories, specially selected and adapted to meet the child and the child in all of us